PERILAKU MEROKOK DAN KEMATANGAN EMOSI SISWA SMAN 7 PEKANBARU - Zellitri Surti; Zulfan Saam; Tri Umari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The aimof this research is to know the smoking behavior and the ripeness students emotional who smoking in SMAN 7. The method of this research is descriptive qualitatif methods. The isntrument of this research is there are 2 items of open ended questionnaire, 30 items of closedended question naire for smoking, and 17 items for the emotional ripeness. The data technique analyzing is counting the question naire score that got from student by using likert scale. In this result, the smoking behavior influenced by society, where the student shave the place for hang out and meet each other, And when students smoking in school, also the student who smoking, they almost impolite and uno bedience with their parents when they are wishes unfulfilled.Keywords: Smoking behavior, students emotional ripeness